Study of geometries and electronic properties of AgSin clusters using DFT/TB - Ziella, Daniel Horacio (2011)
We present a theoretical study of the structures of silver silicon clusters, AgSin, n = 1–15, using density functional tight binding methods. We discuss in detail the search for silicon clusters stabilized by silver dopage, their dissociation paths, and electronic properties. We also investigate the properties of silver encapsulated structures and compare them with those obtained when replacing the silver atom by different metals. Our results are checked against experimental measurements when available. © 2010 Wiley Periodicals, Inc. Int J Quantum Chem 111: 1680–1693, 2011